+0  
 
-1
74
1
avatar+88 

Use trigonometric identities to simplify the following expressions:

 

a) cos²θ(1+tan²θ)

 

b) tan²θ-sec²θ+sin²θ+cos²θ

 Apr 22, 2020
 #1
avatar+21931 
+1

a)  cos2(x) · ( 1 + tan2(x) )  =  cos2(x) + cos2(x) ·tan2(x)  =  cos2(x) + cos2(x) · sin2(x) / cos2(x)

                                                                                          =  cos2(x) + sin2(x)  =  1

 

b)  tan2(x) - sec2(x) + sin2(x) + cos2(x)  =  tan2(x) - sec2(x)  =  tan2(x) - [ 1 + tan2(x) ]

                                                                                              =  tan2(x) - 1 - tan2(x)

                                                                                              =  -1

 Apr 23, 2020

8 Online Users

avatar